Improving adherence to healthy dietary patterns, genetic risk, and long term weight gain: gene-diet interaction analysis in two prospective cohort studies - T. Wang; Heianza, Y.; Sun, D.; Huang, T.; W. Ma; Rimm, E. B.; Manson, J. E.; Hu, F. B.; Willett, W. C.; Qi, L. (BMJBMJ, 2018)
OBJECTIVE: To investigate whether improving adherence to healthy dietary patterns interacts with the genetic predisposition to obesity in relation to long term changes in body mass index and body weight. DESIGN: Prospective cohort study. SETTING: Health professionals in the United States. PARTICIPANTS: 8828 women from the Nurses' Health Study and 5218 men from the Health Professionals Follow-up Study. EXPOSURE: Genetic predisposition score was calculated on the basis of 77 variants associated with body mass index. Dietary patterns were assessed by the Alternate Healthy Eating Index 2010 (AHEI-2010), Dietary Approach to Stop Hypertension (DASH), and Alternate Mediterranean Diet (AMED). MAIN OUTCOME MEASURES: Five repeated measurements of four year changes in body mass index and body weight over follow-up (1986 to 2006). RESULTS: During a 20 year follow-up, genetic association with change in body mass index was significantly attenuated with increasing adherence to the AHEI-2010 in the Nurses' Health Study (P=0.001 for interaction) and Health Professionals Follow-up Study (P=0.005 for interaction). In the combined cohorts, four year changes in body mass index per 10 risk allele increment were 0.07 (SE 0.02) among participants with decreased AHEI-2010 score and -0.01 (0.02) among those with increased AHEI-2010 score, corresponding to 0.16 (0.05) kg versus -0.02 (0.05) kg weight change every four years (P<0.001 for interaction). Viewed differently, changes in body mass index per 1 SD increment of AHEI-2010 score were -0.12 (0.01), -0.14 (0.01), and -0.18 (0.01) (weight change: -0.35 (0.03), -0.36 (0.04), and -0.50 (0.04) kg) among participants with low, intermediate, and high genetic risk, respectively. Similar interaction was also found for DASH but not for AMED. CONCLUSIONS: These data indicate that improving adherence to healthy dietary patterns could attenuate the genetic association with weight gain. Moreover, the beneficial effect of improved diet quality on weight management was particularly pronounced in people at high genetic risk for obesity.
Keywords: Adult; Aged; Body Mass Index; Diet/adverse effects/*methods; Female; Follow-Up Studies; Genetic Predisposition to Disease/epidemiology/genetics; Genotype; Health Personnel/statistics & numerical data; Healthy Diet/psychology/*trends; Humans; Male; Middle Aged; Nurses/statistics & numerical data; Obesity/epidemiology/*genetics; Outcome Assessment (Health Care); Prospective Studies; Treatment Adherence and Compliance/statistics & numerical data; United States/epidemiology; Weight Gain/*genetics